Error rate and outage of dual‐hop DF relay system with selection combining over Rice fading. (21st June 2018) - Dixit, Dharmendra; Sahu, P. R.
Summary: Performance of dual‐hop decode‐and‐forward relay system with selection‐combining receiver is analyzed over Rice fading channels. The following closed‐form expressions of performance metrics are derived: moment generating function for selection‐combining receiver output signal‐to‐noise ratio, exact average bit error rate of noncoherent modulations, approximate average symbol error rate for coherent modulations, and outage probability. We also obtain simple asymptotic expressions for moment generating function, exact average bit error rate, average symbol error rate, and outage probability, which are useful to characterize the diversity order and the coding gain. The optimal power allocation analysis suggests that the optimal power allocation factor is independent of total signal‐to‐noise ratio and source‐to‐destination link fading parameters. The accuracy of the obtained analytical expressions are supported by computer simulation results. Abstract : The key findings include the following: (1) derived exact closed‐form moment generating function expression for SC receiver output signal‐to‐noise ratio; (2) derived exact closed‐form and asymptotic closed‐form expressions for average bit/symbol error rate and outage probability; and (3) optimum power allocation analysis and obtained a closed‐form expression of optimal power allocation factor.